The existence of experimental sinusitis in rats and the place of bromhexine as a mucolytic nose drop in the treatment of sinusitis - Koyuncu, M.; Yilmaz, M.; Yalcin, S.; Metin, N.; Gunduz, S.; Karatas, E. (My University, 1989)
[Abstract Not Available]
Keywords: Administration, Intranasal; Animal; Bromhexine; Disease Models, Animal; Drainage; English Abstract; Rabbits; Sinusitis; bromhexine; bromhexine; animal experiment; article; biological model; experimental infection; nonhuman; nose secretion; oral drug administration; rabbit; sinusitis; streptococcus pneumoniae; animal; disease model; intranasal drug administration; sinusitis; wound drainage